1984
DOI: 10.1007/bf01870573
|View full text |Cite
|
Sign up to set email alerts
|

Monocarboxylic acid permeation through lipid bilayer membranes

Abstract: The membrane permeability coefficients for the homologous monocarboxylic acids, formic through hexanoic, as well as benzoic and salicylic, were determined for egg phosphatidylcholine-decane planar bilayer membranes. The permeabilities of formic, acetic and propionic acid were also determined for "solvent-free" phosphatidylethanolamine bilayers. Permeability coefficients were calculated from tracer fluxes measured under otherwise symmetrical conditions, and precautions were taken to ensure that the values were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
162
1
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(180 citation statements)
references
References 38 publications
16
162
1
1
Order By: Relevance
“…[30] This finding violates the Meyer-Overton rule in two respects: i) P M,SA is unreasonably low. From the octanol water partition coefficient K p ≈300, [31] Equation (1) (3) that is, the difference between P M,SA− and P M,SA should be three orders of magnitude larger than has been reported. [30] The reason for the discrepancy between theory and experiment becomes evident, if the limitations of the experimental approach are considered.…”
Section: Aromatic Weak Acidsmentioning
confidence: 87%
See 1 more Smart Citation
“…[30] This finding violates the Meyer-Overton rule in two respects: i) P M,SA is unreasonably low. From the octanol water partition coefficient K p ≈300, [31] Equation (1) (3) that is, the difference between P M,SA− and P M,SA should be three orders of magnitude larger than has been reported. [30] The reason for the discrepancy between theory and experiment becomes evident, if the limitations of the experimental approach are considered.…”
Section: Aromatic Weak Acidsmentioning
confidence: 87%
“…In perfect agreement with the Meyer-Overton rule, the same authors found 1.1 cm s −1 for hexanoic acid. [31] It is thus safe to conclude that the study by Grime et al [39,42] was hampered by UL effects. UL limitations led to severe underestimations of P M for all carboxylic acids in their system.…”
Section: Transport Of Short-chain Carboxylic Acids Through Membranesmentioning
confidence: 96%
“…This implies that at the prevailing pH values of the colonic lumen (pH 6-7.5; Cummings et al, 1987), at least 90% of all SCFAs exist in the ionized (anionic) form. Despite a relative abundance of the anionic form, it is difficult to predict whether the transmembrane fluxes of any one molecular form will predominate because nonionic diffusion is extremely rapid across many artificial and cellular membranes (Roos and Boron, 1981;Walter and Gutknecht, 1984;Montrose and Kimmich, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some weak acid protonophores may also exert detrimental effects on cellular processes such as oxidative phosphorylation, apoptosis (7), and photosynthesis (8). The transport of weak acids across model cell membranes and the determination of permeation rates have consequently been the subject of a considerable number of studies (9)(10)(11)(12)(13)(14)(15)(16)(17)). …”
mentioning
confidence: 99%